THE DETERMINATION OF THE MORPHOLOGICAL TYPES OF GALAXY CLUSTERS USING CLUSTER CARTOGRAPHY - Panko, E. A.; Emelyanov, S. I. (Одеські астрономічні публікації, 2016)
We discuss the possibility of using the Cluster Cartography set for the determined the morphological types of galaxy clusters. The applied morphological scheme was proposed by Panko (2013). The morphological types are determined using numerical criteria based on three parameters: concentration to the cluster center, the signs of preferential direction or plane in the cluster (filamentary substructure), and the positions of the brightest galaxies. However, structures like galaxy clusters need visual preview for classification. The Cluster Cartography set constructs the individual cluster map in different forms and allows to estimate previously cluster type.